The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/21505594.2018.1556151
|View full text |Cite
|
Sign up to set email alerts
|

The Yersinia pseudotuberculosis Cpx envelope stress system contributes to transcriptional activation of rovM

Abstract: The Gram-negative enteropathogen Yersinia pseudotuberculosis possesses a number of regulatory systems that detect cell envelope damage caused by noxious extracytoplasmic stresses. The CpxA sensor kinase and CpxR response regulator two-component regulatory system is one such pathway. Active Cpx signalling upregulates various factors designed to repair and restore cell envelope integrity. Concomitantly, this pathway also down-regulates key determinants of virulence. In Yersinia, cpxA deletion accumulates high le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…The regulation capacity of CpxAR affects different virulence-related features, mostly depending on the species, including adherence to host tissues, resistance to serum, expression of toxin secretion systems, cellular invasion capacity, biofilm formation, and so on. But paradoxically, the CpxAR response seemingly exerts an activator effect on virulence factors in some species (Debnath et al 2013 , Bontemps et al 2015 , Li et al 2018 , Xie et al 2018 ), whereas its role is apparently repressor in others (Liu et al 2012 , Acosta et al 2015 , De la Cruz et al 2015 , 2016 , Thanikkal et al 2019 , Vogt et al 2019 ). These interesting particularities could be due to the ligand(s) that the CpxA sensor may bind, that could change depending on the scenario in which bacteria find themselves at each moment.…”
Section: Cpxar Systemmentioning
confidence: 99%
“…The regulation capacity of CpxAR affects different virulence-related features, mostly depending on the species, including adherence to host tissues, resistance to serum, expression of toxin secretion systems, cellular invasion capacity, biofilm formation, and so on. But paradoxically, the CpxAR response seemingly exerts an activator effect on virulence factors in some species (Debnath et al 2013 , Bontemps et al 2015 , Li et al 2018 , Xie et al 2018 ), whereas its role is apparently repressor in others (Liu et al 2012 , Acosta et al 2015 , De la Cruz et al 2015 , 2016 , Thanikkal et al 2019 , Vogt et al 2019 ). These interesting particularities could be due to the ligand(s) that the CpxA sensor may bind, that could change depending on the scenario in which bacteria find themselves at each moment.…”
Section: Cpxar Systemmentioning
confidence: 99%
“…RovA, a global transcriptional regulator that activates the expression of invasin, is directly regulated by CpxR (Carlsson et al, 2007b). A further level of control was recently discovered when it was demonstrated that RovM, a regulator of RovA that represses its expression during nutrient limitation, was found to be directly CpxR-P regulated (Heroven and Dersch, 2006; Heroven et al, 2008; Thanikkal et al, 2019). Thus, RovA expression is not only modulated by CpxR at its own promoter, but also through CpxR upregulation of RovM.…”
Section: The Cpxra Two-component Systemmentioning
confidence: 99%
“…Follow-up work will need to establish whether these pathways work independently or through Cpx-signalling. We have already established existence of a CpxR-RovM-RovA regulatory cascade for the control of Yptb adhesion 49 , 50 and a CpxR-RcsA-RcsB regulatory cascade for the control of Yptb Ysc-Yop type III secretion 51 . Hence, it could be that these regulatory cascades may extend the influence of Cpx-signalling to fine-tuning biofilm development.…”
Section: Discussionmentioning
confidence: 99%
“…From earlier work on Yptb , the classical CpxAR two-component signalling system is involved in modulating the regulatory cascade outputs of RovA-RovM 49 , 50 and the Rcs phosphorelay system 51 . These couplings suggests that Cpx-signalling might also be involved in controlling aspects of biofilm development.…”
Section: Introductionmentioning
confidence: 99%